Nature in minds : Jaques Gandebeuf meeting Icelanders, Swedes and Norwegians - Loftsson, Elfar; Lohm, Ulrik; Skúlason, Páll (Tema vatten i natur och samhälle, 2006)
The series of interviews presented in this book were originally conceived as a part of a wider project, investigating the ways in which Nordic people relate to nature. That project, entitled “Nature, National Identity and Environmental Policy in the Nordic Countries”, was initiated in 1995 by Elfar Loftsson and Ulrik Lohm from the University of Linköping; Páll Skúlason and Þorvarður Árnason from the University of Iceland; and Lars Henrik Schmidt from the University of Århus. The project was intended from the outset to be interdisciplinary, with sociological, anthropological and philosophical methods to be applied in the investigation. Originally, the project involved three Nordic countries: Sweden, Denmark and Iceland. Parts of the project were undertaken in all three countries so that it would be possible to compare the results, whilst other parts were carried out separately in each country. The largest common sub-project was a questionnaire survey that was carried out in 1997 and investigated views of nature, and environmental concerns, amongst the general public in Sweden, Denmark and Iceland.In connection with the questionnaire survey, it was decided to invite an experienced journalist to join in the project and to ask him to interview people with various backgrounds, in order to elicit from them, in a personal manner, their ways of valuing and relating to nature. In addition to being of interest in themselves, the interviews were intended to complement the other parts of the project. Páll Skúlason had worked earlier with Jacques Gandebeuf when he came to Iceland in the wake of the volcanic eruption in the Westman Islands in 1972 to interview people about their experiences of living in a close Páll Skúlason and dangerous relationship with nature. Thus, Páll knew about Jacques´ skills as an interviewer, his great experience as an environmentalist, and his remarkable talent as a writer; and it was agreed to ask him to do the job. He accepted the assignment, and in this book the reader is presented with the ...